Balloon pulmonary valvotomy as interim palliation for symptomatic young infants with tetralogy of Fallot - Remadevi K; Vaidyanathan Balu; Francis Edwin; Kannan B.R.J; Kumar Raman (Wolters Kluwer Medknow Publications, 2008)
Objectives: To describe the case selection, technique and immediate and short-term results of balloon pulmonary valvotomy (BPV) in young infants with tetralogy of Fallot (TOF). Background: Symptomatic young infants with TOF can either undergo corrective surgery or Blalock-Taussig (BT) shunt. Corrective surgery in early infancy is associated with significant morbidity and is not a realistic option in many centers. BT shunt carries the risk of branch pulmonary artery distortion and shunt occlusion. Methods : Infants less than three months with a significant valvar pulmonary stenosis (with or without associated infundibular and annular component) and oxygen saturation ≤ 80% were offered BPV. The right ventricular outflow tract (RVOT) was crossed with 4F Judkin′s right coronary catheter and the valve was crossed with 0.014" coronary guide wire. Serial balloon dilatations were done with over the wire coronary balloons (3-4 mm) and Mini Tyshak balloons up to a balloon annulus ratio of 2:1, depending upon the improvement in saturation and formation of annular waist. Results : Seventeen infants less than three months of age with tetralogy of Fallot (median age: 33 days, range: 10-90 days, weight: 3.47 ± 0.87 kg, pulmonary annulus Z score: -5.59 ± 1.04) including eight neonates underwent palliative BPV between May 2004 and March 2007. The mean balloon annulus ratio was 1.4 ± 0.28 and fluoroscopy time was 26.18 ± 20.2 minutes. The mean oxygen saturation increased significantly from 73 ± 7% to 90 ± 3.68% following BPV (p = 0.0001). The only major complication was RVOT perforation and pericardial tamponade in one infant. The mean follow-up period was 23 ± 12 months. Two babies developed significant desaturation requiring surgery in the six months following BPV. There was a significant increase in pulmonary annulus. The z score for the pulmonary annulus improved from -5.59 ±1.04 before BPV to - 4.31 ± 1.9 at the time of last follow-up (p = 0.018). The mean Z score of hilar right pulmonary artery (RPA) increased significantly from -1.19 ± 1.78 before BPV to 0.7 ± 0.91 after BPV (p = 0.001). The mean Z score of hilar left pulmonary artery (LPA) increased significantly from -1.28 ± 1.41 to 0.03 ± 1.29 after BPV (p = 0.005). Eight patients underwent corrective surgery. Conclusions : Balloon pulmonary valvotomy is safe and effective. It significantly improves the growth of pulmonary annulus and branch pulmonary arteries. Thus it can be considered as an interim palliative procedure for symptomatic young infants with TOF and predominant valvar pulmonary stenosis.